Effects of handedness consistency and saccade execution on eyewitness memory in cued- and free-recall procedures*. Issue 9 (21st October 2018) - Lyle, Keith B.
ABSTRACT: Identifying characteristics that distinguish between people with relatively good versus poor episodic memory is an important goal of eyewitness-memory research, as is identifying activities that can improve people's ability to retrieve episodic memories. Consistency of hand preference is a trait associated with the quality of people's episodic memory and repetitive saccade execution is an activity known to improve people's ability to retrieve episodic memories. These factors were examined in relation to cued and free recall of a staged criminal event. Individuals with inconsistent hand preference (versus consistent) remembered more on a cued-recall test and also freely recalled a larger amount of victim information. Repetitive saccade execution did not increase cued recall but did increase free recall of victim information. Theoretical implications are discussed, as is potential practical significance, with an emphasis on the size of the observed effects.